Acute cervical epidural hematoma: case report - GUILHERME BORGES; LEONARDO BONILHA; MARCOS VINICIUS CALFAT MALDAUM; JOSÉ RIBEIRO MENEZES; VERÔNICA ZANARDI (Arquivos de Neuro-Psiquiatria)
A 74 year-old patient with a nocturnal onset of neck and chest pain was brought to an emergency clinic. Physical examination and cardiac assessment were normal. Three hours after the addmittance, a flaccid paralysis of the four limbs supervened. Suspecting of an unusual onset of central nervous system infection, a lumbar puncture was performed, yielding 20 ml of normal cerebrospinal fluid. Thirty oinutes after the puncture, the patient completely regained neurological funcion. He was then referred to a General Hospital where a computed tomography (CT) scan was done showing a large cervical epidural bleeding in the posterolateral region of C4/C5 extending to C7/Th1, along with a C6 vertebral body hemangioma. A magnetic resonance imaging revealed the same CT findings. A normal selective angiography of vertebral arteries, carotid arteries and thyreocervical trunk was carried out. Spontaneous spinal epidural hematoma (ASSEH) is a rare but dramatic cause of neurological impairment. In this article we report a fortunate case of complete recovery after an unusual spine cord decompression. We also review the current literature concerning diagnosis and treatment of ASSEH.